Princess Jellyfish. 02 - Higashimura, Akiko (Princess Jellyfish, 2016)
"With the geeky paradise of Amamizu-kan threatened by redevelopment plans, Tsukimi and Amars must spring into action. But the wily Inari-san and her hold on Shu forces Kuranosuke to pull out all the stops: money, blackmail, and ... fashion?! Though Amamizu-kan still struggles with Kuranosuke's stylish ways, the neighborhood fashionista has too much to lose, whether it's a hidden identity or priceless friendships. Tsukimi gets the chance to make her jellyfish dreams into a glamorous reality, but that means breaking out of her bubble! Can these misfit princesses save their castle?"--Back cover.